Own-price and cross-price elasticities of demand for cigarettes and waterpipe tobacco in three Eastern Mediterranean countries: a volumetric choice experiment. Issue 1 (30th June 2021) - Chalak, Ali; Nakkash, Rima; Abu-Rmeileh, Niveen M E; Khader, Yousef S; Jawad, Mohammed; Mostafa, Aya; Abla, Ruba; Louviere, Jordan; Salloum, Ramzi G
Abstract : Background: Waterpipe tobacco smoking rates in the Eastern Mediterranean region are among the highest worldwide, yet little evidence exists on its economics. Estimates of demand elasticities for tobacco products are largely limited to cigarettes. This study aimed to estimate own-price and cross-price elasticities of demand for cigarettes and waterpipe tobacco products in Lebanon, Jordan and Palestine. Methods: A volumetric choice experiment was conducted using nationally representative household surveys. The choice experiment elicited respondents' stated purchases of eight cigarette and waterpipe tobacco product varieties by hypothetically varying prices. Data were analysed using zero-inflated Poisson models that yielded demand elasticity estimates of cigarette and waterpipe tobacco consumption. Results: The study included 1680 participants in Lebanon (50% female), 1925 in Jordan (44.6% female) and 1679 in Palestine (50% female). We found the demand for premium cigarettes to be price elastic (range, −1.0 to −1.2) across all three countries, whereas the demand for discount cigarettes was less elastic than premium cigarettes in Lebanon (−0.6) and Jordan (−0.7) and more elastic in Palestine (−1.2). The demand for premium waterpipe tobacco was highly elastic in Lebanon (−1.9), moderately elastic in Jordan (−0.6) and inelastic in Palestine (0.2). The cross-price elasticity between cigarettes and waterpipe tobacco was near zero, suggesting that the two products are not considered to be close substitutes by consumers. Conclusions: These results serve as a strong evidence base for developing and implementing fiscal policies for tobacco control in the Eastern Mediterranean region that address cigarettes and waterpipe tobacco products.